Liberia : Enhanced Initiative for Heavily Indebted Poor Countries; Preliminary Document. (IMF Staff Country Reports; Country Report ;, 2008)
This paper presents a preliminary assessment of the eligibility of Liberia for assistance under the Enhanced HIPC Initiative. It describes recent economic progress and the situation of Liberia. The study discusses its medium- to long-term macroeconomic framework and poverty reduction strategy. It also summarizes the preliminary Debt Relief Analysis (DRA) and presents the size of possible Heavily Indebted Poor Countries (HIPC), Multilateral Debt Relief Initiative (MDRI), and MDRI-type assistance, including arrears clearance. It also suggests a timeline for preparing the decision point document, and outlines reforms that could serve as completion point triggers.